The The Effectiveness of ChatGPT Integration in Improving English Learning Autonomy in Senior High Schools (SMA) in Banda Aceh City - Meta Keumala; Zakaria (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
The rapid development of artificial intelligence (AI) has introduced new opportunities for language learning, particularly through tools such as ChatGPT. Despite its global use, the ChatGPT application in Indonesian high schools remains limited, particularly in supporting independent learning under the Independent Curriculum. This study investigated the effectiveness of ChatGPT in enhancing students’ English learning independence, with a focus on engagement, motivation, and performance. A mixed-methods design was applied in three Banda Aceh schools (SMA 3, SMA 4, and SMA 5). Data were gathered through pre-tests and post-tests with 102 students divided into experimental groups using ChatGPT and control groups using conventional methods. Quantitative data were analysed using descriptive statistics, the Shapiro-Wilk test, Levene’s test, and paired sample t-tests, while qualitative data were examined thematically. Results showed significant improvement across schools. SMA 3 increased from a pretest mean of 80.39 to a posttest mean of 94.17 (t = 16.60, p = 3.646e-18). SMA 4 rose from 74.00 to 91.00 (t = 23.49, p = 5.164e-23), while SMA 5, with the lowest baseline (57.10), reached 83.93 (t = 17.09, p = 1.106e-16). Homogeneity tests indicated pretest variances differed (p = 0.001), but posttest variances became homogeneous (p = 0.650). The novelty of this study lies in showing that ChatGPT not only improved achievement but also reduced variability among students. In conclusion, ChatGPT effectively fostered independent English learning, balanced student outcomes, and offered a promising tool for adaptive, self-directed learning in Indonesian high schools.